Video Rate Control Using Fourier Transform - et. al., Tashmanov E.B, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper studies the control of the video data transmission rate by the compression parameters based on the Fourier transform. The Dirichlet problem for the Poisson equation is considered.